Learning interventions in the WHO Eastern Mediterranean region: supporting Member States to get prepared for better response to health emergencies in the region - Elhakim, Mohamed; Hammoud, Samar Dimachkie; Gmach, Sabri; Albadri, Jehan; Mahrous, Heba; Arifi, Fatima; Abdel Latif, Nisreen; Moussa, Safaa; Anan, Huda; Saidouni, Asma; Ghazy, Ramy Mohamed; Elkholy, Amgad; et al. (Frontiers in Public Health, 2024)
Background The Eastern Mediterranean Region (EMR) faces numerous public health risks caused by biological, chemical, man-made, and natural hazards. This manuscript aimed to assess the multifaceted interventions and strategies used to strengthen the EMR’s preparedness capacities to respond properly to current and upcoming health emergencies. Objective To address these challenges, it is crucial to implement comprehensive and robust strategic risk assessments and health emergency preparedness frameworks. The World Health Organization (WHO) takes a risk-based approach, emphasizing the significance of all-hazards emergency management and the creation of national health risk profiles using the Strategic Toolkit for Assessing Risk (STAR). Furthermore, the International Health Regulations (IHR) Monitoring and Evaluation Framework (MEF) ensures continuous learning and capacity building among Member States, enhancing their ability to manage health emergencies effectively. Key components include State Party Annual Reporting (SPAR), Joint External Evaluation (JEE), After Action Review (AAR), Intra Action Review (IAR), and Simulation Exercises (SimEx). Moreover, initiatives like One Health, Emergency Care Systems, Safe Hospitals, and Public Health Emergency Operations Centers (PHEOCs) reinforce preparedness and response capacities. Risk communication and community engagement (RCCE) strategies play a pivotal role in disseminating timely information and fostering community resilience. Furthermore, the management of Chemical, Biological, and Radiological (CBRN) incidents remains a priority, necessitating collaboration between the public health and security sectors. This comprehensive approach aims to strengthen health systems, reduce risks, and improve emergency response capabilities throughout the EMR, thereby promoting global health security and resilience. Conclusion The EMR is addressing public health challenges through frameworks like IHR-MEF, and RCCE. It is strengthening emergency care systems, ensuring safe hospitals, and establishing PHEOCs. Proactive measures to address CBRN events and collaboration are enhancing resilience. The inclusion of the One Health approach underscores the EMR’s holistic strategy to address the health threats at the human-animal-environment interface. This demonstrates the EMR’s commitment to global health security.